The Effect of a Proposed Online Educational Platform in Manipulating Students’ Reading and Writing Problems (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The present study has aimed to identify the effect of a proposed online educational platform inmanipulating students’ reading and writing problems. The study followed the quasi-experimentalapproach. A number of 50 students were selected out of the students of primaryschoolat MaimounaBint Al-Harith Primary School who face problems in reading and writing. Such students made upthe sample of the study for the second semester 2020/21. They were taught digital educationalcontent through the prepared online educational platform.In order to achieve the objectives of thestudy, an achievement test (pretest – diagnostic test – posttest). It was designed of 24 questions, andits validity and reliability indications were pointed out.The results of the study showed that there were statistically significant differences in thearithmetic mean of students' performance in the posttest due to the use of the online platform.Thestudy concluded with several recommendations, including the adoption of the proposed educationalonline platform to manipulate students' reading and writing problems